ParaCEST Agents Encapsulated in Reverse Nano-Assembled Capsules (RACs): How Slow Molecular Tumbling Can Quench CEST Contrast - Farashishiko, Annah; Slack, Jacqueline R.; Botta, Mauro; Woods, Mark (Frontiers in Chemistry, 2018)
Although paraCEST is a method with immense scope for generating image contrast in MRI, it suffers from the series the serious drawback of high detection limits. For a typical discrete paraCEST agent the detection limit is roughly an order of magnitude higher than that of a clinically used relaxation agent. One solution to this problem may be the incorporation of a large payload of paraCEST agents into a single macromolecular agent. Here we report a new synthetic method for accomplishing this goal: incorporating a large payload of the paraCEST agent DyDOTAM3+ into a Reverse Assembled nano-Capsule. An aggregate can be generated between this chelate and polyacrylic acid after the addition of ethylene diamine. Subsequent addition of polyallylamine hydrochloride followed by silica nanoparticles generated a robust encapsulating shell and afforded capsule with a mean hydrodynamic diameter of 650 ± 250 nm. Unfortunately this encapsulation did not have the effect of amplifying the CEST effect per agent, but quenched the CEST altogether. A significant proportion of the quenching effect of encapsulation could be attributed to the effect of slowing molecular tumbling, which is inevitable when the chelate is incorporated into a nano-scale material. This increases the transverse relaxation rate of chelate protons and a theoretical examination using Solomon Bloembergen Morgan theory and the Bloch equations shows that the increase in the transverse relaxation rate constant for the amide protons, in even modestly sized nano-materials, is sufficient to significantly quench CEST.